Research on the Dispatching Rules of Inter-Basin Water Transfer Projects Based on the Two-Dimensional Scheduling Diagram - Cai, Siyu; Sun, Long; Liu, Qingtao; Ji, Yi; Wang, Hao (Frontiers in Earth Science, 2021)
Inter-basin water transfer projects play an important role in allocating water resources that vary both in temporal and spatial scale while supporting regional development. In the practical operation of inter-basin water transfer projects, high water level and less inflow runoff would result in water supply destruction, while low water level and more inflow runoff would cause abandoned water. How to play the compensation roles of hydrological characteristics and storage capacities of multi-reservoirs to maximize the utilization efficiency of water resources, the key is to select the basis for the decision-making of starting water transfer process. In this paper, we selected the “Datong-Huangshui” water transfer project as the research subject, analyzed the composition of the inter-basin water transfer system, and constructed a dispatching rule extraction model including water transfer rules, water diversion rules, and water supply rules. Then the NSGA-II was used to solve the multi-objective optimization model to obtain the Pareto frontier solution set of the dispatching rules. Finally, the optimal operation scheme was determined and discussed according to the scheduling scheme decision model. The model itself was based on the gray target model and prospect theory. We found that: (1) The optimal target frontier obtained by the two-dimensional scheduling diagram and the hedging rules for water supply was closer to the theoretical optimal frontier of the multi-objective problem. This result indicated that the two-dimensional scheduling diagram and the hedging rules for water supply could better guide the water diversion operation of inter-basin water transfer projects. (2) Based on the multi-objective optimal operation schemes set, the OPT scheme obtained by the scheduling scheme decision model using gray target model and prospect theory could generate 359 million Kwh. At the same time, it could guarantee 90% of municipal and industrial water supply and 85% of agricultural water supply.